The Nuns' Learning Motivation - Yulius Sodah (Jurnal Indonesia Sosial Teknologi, 2024)
Nuns are a group of Catholic women who choose not to marry in order to focus on special service in the Church according to the rules of the congregation. Some nuns undergo study missions or become female students on public campuses. This research specifically wants to examine how the learning motivation of students who are nuns is. Researchers want to find out how they increase their motivation to learn while still carrying out the demands of the community or institute. This study uses a qualitative method conducted on 4 nuns who are undergoing studies at a university in Yogyakarta. The results of the study showed that they had a unique motivation to learn. The nuns have an intrinsic motivation to learn, namely the desire and awareness to complete their studies quickly. Obedience to the task of community mission is the most powerful extrinsic motivation that influences the ability and interest in learning of Catholic nuns. The mission task gives birth to motivation from within (intrinsic), namely the responsibility to complete the task entrusted to it by the congregation. The nuns also face challenges in studying, especially adjusting themselves due to different ages and the demands of life as nuns. Further research needs to pay attention to the frequency and intensity of interviews and needs to involve other parties who know the nuns who are studying.